Assessment of postoperative prognosis in patients with acute ST-segment elevation myocardial infarction after PCI using LRP1 - Guan, Jingwen; Xu, Yikang; Liu, Limin; Su, Mengran; Ma, Jingru (Frontiers in Cardiovascular Medicine, 2025)
PurposeTo evaluate the prognostic value of Low-density lipoprotein receptor-related protein 1 (LRP1) in patients with acute ST-segment elevation myocardial infarction (STEMI) following percutaneous coronary intervention (PCI).MethodThis prospective study included 96 STEMI patients who underwent PCI and 19 control subjects with normal coronary arteries. Coronary blood was taken from both groups, and LRP1 expression levels were quantified using real-time quantitative PCR (qPCR). The STEMI patients were stratified into low, middle, and high LRP1 groups based on tertiles of LRP1 expression. The primary endpoint was the occurrence of major adverse cardiovascular events (MACE) during a six-month follow-up period post-PCI.ResultsLRP1 expression in arterial blood was significantly lower in the STEMI group [0.63(0.23,1.1)] compared to the control group [1.5(0.84,1.85)] (P < 0.05). The incidence of MACE showed an increasing trend across the LRP1 tertiles: 6.7% (95% CI: 1.9–21.3%) in the low LRP1 group, 22.6% (95% CI: 11.4–39.8%) in the middle LRP1 group, and 41.9% (95% CI: 26.4–59.2%) in the high LRP1 group. The high LRP1 group exhibited a significantly higher MACE rate compared to the low LRP1 group (P < 0.05). Spearman's rank correlation analysis revealed positive correlations between LRP1 and both NT-proBNP and cTnT (r = 0.349, 95% CI: 0.156–0.515, P < 0.001; r = 0.328, 95% CI: 0.133–0.497, P = 0.001, respectively), and a negative correlation with LVEF values (r = −0.285, 95% CI: −0.460 to −0.087, P = 0.006). Receiver operating characteristic (ROC) analysis identified an LRP1 expression threshold of 0.79 for predicting MACE within six months post-PCI, with a sensitivity of 81.8% (95% CI: 61.5–92.7%), a specificity of 70% (95% CI: 58.5–79.5%), and an area under the curve (AUC) of 0.789 (95% CI: 0.688–0.890, P < 0.001).ConclusionLRP1 expression appears to be an independent predictor of MACE in STEMI patients and may have prognostic value for short-term outcomes following PCI.